2009
DOI: 10.1074/jbc.m109.039479
|View full text |Cite
|
Sign up to set email alerts
|

Conserved Negative Charges in the N-terminal Tetramerization Domain Mediate Efficient Assembly of Kv2.1 and Kv2.1/Kv6.4 Channels

Abstract: Voltage-gated potassium (Kv) channels are transmembrane tetramers of individual ␣-subunits. Eight different Shaker-related Kv subfamilies have been identified in which the tetramerization domain T1, located on the intracellular N terminus, facilitates and controls the assembly of both homoand heterotetrameric channels. Only the Kv2 ␣-subunits are able to form heterotetramers with members of the silent Kv subfamilies (Kv5, Kv6, Kv8, and Kv9). The T1 domain contains two subdomains, A and B box, which presumably … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
34
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 44 publications
3
34
1
2
Order By: Relevance
“…2a) which has specificity for conducting K ? ions (Bocksteins et al 2009). Auxiliary b-subunit assembles into tetrameric structures and interacts with a-subunit of K v channel which provides a role in modulating channel gating kinetics (Gulbis et al 1999).…”
Section: Potassium Channel Structurementioning
confidence: 96%
See 1 more Smart Citation
“…2a) which has specificity for conducting K ? ions (Bocksteins et al 2009). Auxiliary b-subunit assembles into tetrameric structures and interacts with a-subunit of K v channel which provides a role in modulating channel gating kinetics (Gulbis et al 1999).…”
Section: Potassium Channel Structurementioning
confidence: 96%
“…Each a-subunit of voltage-gated potassium channel (K v ) comprised six transmembrane helical segments (S1-S6) with a cytoplasmic N-and C-termini. N-terminus have T1 domain (tetramerization domain) that assembles the a-subunits into functional channel (Zerangue et al 2000;Bocksteins et al 2009), while S4 segment is highly positive and acts as voltage sensor along with the loop between S5-S6 (Yost 1999). Pore region contains the signature sequence GYG (Fig.…”
Section: Potassium Channel Structurementioning
confidence: 99%
“…When a trafficking deficiency causes the lack of functional membrane proteins at the PM, FRET could still be observed in the ER while a tetramerization deficiency would also eliminate FRET in the ER. With this approach, it has been demonstrated that the reduced PM expression of mutant Kv2.1 channels was due to a tetramerization deficiency, since the observed reduced current amplitude of those mutant channels was accompanied by a significant reduction of FRET in the ER (Bocksteins et al, 2009). …”
Section: Fluorescence Resonance Energy Transfer (Fret)mentioning
confidence: 99%
“…In addition to using FRET to investigate whether two proteins of interest only co-localize or actually interact with each other, FRET can also be used to ascertain whether the lack of functional membrane proteins at the PM is due to a trafficking or tetramerization deficiency (Bocksteins et al, 2009). For this purpose, the FRET efficiency in both a region that represents the PM and a region that represents the ER has to be determined.…”
Section: Fluorescence Resonance Energy Transfer (Fret)mentioning
confidence: 99%
See 1 more Smart Citation